Comparing the effectiveness of psychological education based on McMaster and Olson model on enhancing family coherence of women teachers - amir mostofi sarkari; mohammad ghamari; Simin Hoseinian (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2019)
This research was aimed to compare effectiveness of psychological education based on MacMaster and Olson model on enhancing family coherence of women teachers. The methodology was semi experimental with pre-posttest and following plan. Statistical Society composes of 550 married women teachers of the Khoramdareh city during 2017-2018 educational year. Statistical sample composed of 45 teachers with lower score in questionnaire of family coherence (Olsen, 1999) that randomly divided in test group 1 test group 2, and a control group that each group composes of 15 teachers. Test groups participated in training sessions and the control group did not receive any specific interventions. After training sessions, posttest implemented for all groups. Collected data analyzed by multivariate analyze (mixed). Results revealed that psychological education based on MacMaster and Olson method is effective in enhancing family coherence of women teachers and this effectiveness was lasting (P < 0.001). Results also showed that effectiveness of these two trainings in are not different. Therefore, it can be concluded that for enhancing family coherence of women teachers, it is useful to use psychological education based on MacMaster and Olson method. Keywords: MacMaster Model, Olson model, family coherence